CIVILINIO PROCESO GLOBALIZAVIMO MECHANIZMAS AR CIVILINIO PROCESO 29-TASIS MODELIS EUROPOS SĄJUNGOJE - Lyubchenko, Maxim Ya. Ya. (Teisė, 2015)
The study of civil procedure harmonization in European juridical doctrine has traditionally been connected with the names of such well-known processualists as M. Cappeletti and M. Storme, as well as with their fundamental works “Access to Justice” (1978–1979)1 and “Approximation of Judiciary in the European Community. Final report” (1993)2. The year 2013 was the 20th jubilee year of “M. Storme’s group” final report publishing; that year and its culmination are considered to be the reason for summarizing and planning the prospects for further development of one of the main civil procedure trends.